Ureteral Diaphragmatic Hernia Treated with Ureteral Stenting: A Case Report and Review of the Literature - Tateki Yoshino; Ayako Itakura; Shinnosuke Fujikawa; Tomoyuki Sugitani; Kazuo Kawakami; Emi Ishibashi; Koji Kodama; Shota Oshima (Case Reports in Urology)
Ureteral diaphragmatic hernia through diaphragmatic defects is an exceptionally rare subset of ureteral hernia with only fourteen such cases reported in English manuscripts. An 85-year-old woman was introduced to our department with right flank pain, fever elevation, and nausea. Urinalysis showed bacteriuria, and Escherichia coli was detected in the urine culture. Blood analysis revealed abnormal findings, including elevated WBC count (10,510/μl) and C-reactive protein (0.28 mg/dl). Computed tomography (CT) of the abdomen demonstrated a defect of the right diaphragmatic crus containing a dilated right ureter with associated hydronephrosis. Retrograde pyelography showed hydronephrosis and dilated ureter loops through the defect of diaphragmatic crus, known as a “curlicue sign,” and the diagnosis was right ureteral diaphragmatic hernia. A ureteral stent was placed on her right side, and the ureter was reducted into the retroperitoneal space. After six months, the ureteral stent was removed, with no subsequent recurrence of the ureteral diaphragmatic hernia at seven months. We reviewed all cases in the literature published in English of ureteral diaphragmatic hernia. While the etiology of ureteral diaphragmatic hernia is unknown, our present case and previous reports suggest that a ureteral diaphragmatic hernia may occur due to hepatic atrophy and/or an elevated position of the right kidney.